Integración de motores de simulación y motores de visualización aplicada a simuladores de entrenamiento - Abbate, Horacio (2022)
In the simulation industry for training purposes, it is of great relevance to generate a visual representation of the simulated environment that presents an adequate degree of realism to guarantee the effectiveness of the exercise. Not all toolsavailable in this area have a realistic display system, or are not open for general use. The objective of this work is the integration of a modeling and simulation system of physical systems with a high-performance three-dimensional imager, using open and standardized tools. In this document, the problems that arise from the communication of both systems in real time are analyzed and attacked and a solution based on the techniques studied is designed and implemented by defining a simulated physical model of movement in the OpenModelica environment and its visualization through an image generator developed with the OpenSceneGraph three-dimensional graphics database, communicating both through the CIGI protocol (Common Image Generator Interface). The purpose of this work is to apply the tools initially developed in training simulation projects of the Ministry of Defense, to finally open them to the rest of the areas of the State and to the community.